2001
DOI: 10.1002/app.1743
|View full text |Cite
|
Sign up to set email alerts
|

Free radical polymerization of nitropropyl acrylates and methacrylates. I. Heat of polymerization

Abstract: ABSTRACT:The heat of polymerization ⌬H p , of nitropropyl(meth)acrylate monomers has been studied by differential scanning calorimetry (DSC) in dynamic and isothermal modes. DSC showed that ⌬H p of 2-nitropropyl(meth)acrylate was surprisingly smaller than that of propyl(meth)acrylate but similar to that of 2,2-dinitropropyl(meth)acrylate. According to molecular structure analysis by a PM3 Hamiltonian in a MOPAC program, the contributing main factor to the lowering of ⌬H p of 2-nitropropyl (meth)acrylate was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…1), which were synthesized by our work group following the method described in previous works [3,[5][6][7] and characterized by GPC, FTIR, and 1 H NMR. Their molecular weight characteristics are listed in Table 1 …”
Section: Experimental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), which were synthesized by our work group following the method described in previous works [3,[5][6][7] and characterized by GPC, FTIR, and 1 H NMR. Their molecular weight characteristics are listed in Table 1 …”
Section: Experimental Materialsmentioning
confidence: 99%
“…For example, Cho et al [5] reported the 2,2-dinitropropyl acrylate polymer (PDNPA) and 2,2-dinitropropyl acrylate-2,2-dinitrobutyl acrylate copolymer (DNPA/DNBA) for the pressable PBX formulations. Lee et al [6] studied free radical polymerization of nitropropyl acrylates and methacrylate. The author investigated the synthesis of PDNPA, PDNBA, P (3, 3-DNBA) and gem-dinitro valerylated polystyrene (GDN-PS) [7][8][9][10], and also discussed the compatibility of 2,2-dinitropropyl acrylate-styrene copolymer with some explosives [11].…”
Section: Introductionmentioning
confidence: 99%
“…The value of ∆Hp for methacrylate groups was assumed to be 58.6 kJ/mol [43]. Experimentally determined values of the heat of polymerization of methacrylate monomers are in the range of 45 to 60 kJ/mol [44][45][46].…”
Section: Characterization Methodsmentioning
confidence: 99%
“…Overall, some of the calculated maximum conversions are above 100%, which is a result of the assumed approximate value of the heat of polymerization. Experimentally determined values of the heat of polymerization of methacrylate monomers can range from 45 to 60 kJ/mol, depending on the structure of the monomer [45][46][47]. According to the literature, conversion values higher than 100% were reported by Andrzejewska (for compositions with 2,2 -thiobisethanol diacrylate (TEDA) and 2,2 -oxybisethanol diacrylate (OEDA)) [48].…”
Section: Uv-dsc Studymentioning
confidence: 99%